Foreign direct investment - Weigel, Dale R. (The World Bank, 1997)
The report reviews lessons from the International Finance Corporation's (IFC) investment, and advisory experience in the developing world, which show the interactions between policy frameworks, and the volume and structure of foreign direct investments (FDI). Case studies show how the Corporation promotes successful project structures, and regulatory changes, as it tries to attain the strongest development impact for investments. In developing countries, FDI has flowed mainly into manufacturing, and processing industries. In the past, investment attractiveness had been closely linked to possession of natural resources, or a large domestic market, while production and trade globalization, competitiveness as a location for investment, and exporting, have become the main determinants of attractiveness. Sources of FDI in the past, came almost exclusively from industrial countries, though recently those sources have widened, emerging from developing countries in their own right, and for their own regions. IFC, as an international initiative to promote FDI in developing countries, is liable to promote bilateral trade agreements, bilateral and multilateral financial institutions, and investment promotion programs; its advisory role may vary from diagnostic studies overviewing constraints to FDI, to investment policy studies giving specific solutions on either changes, or strategies. The study further looks at how policy environment is set, and at finding investor opportunities, through project financing, largely structured as joint ventures. The inherent, fragile nature of joint ventures, restricts foreign ownership, thus limiting project structures; however, careful project design has lead to successful operations, by ensuring management, and financial arrangements.